Yeast Species Mediated Bioprocesses and Bio-Products for Biotechnological Application - Rajesh K. Srivastava (Journal of Biotechnology and Biomedical Science, 2019)
Yeast as unicellular organism, has shown multiple application due to exhibition of noble ability in its cells. And engineered yeast has found more suitability in bioprocesses application as well as adverse conditions adaptation. Different types of yeast strains showed their best capability to adapt the salt and sugar rich environment with their optimal growth capability. These strains, used as suitable and novel cell factories for production of value added bio-products (via utilization of fermentation processes) and also for different types of bioprocesses. Application of yeast species in biotechnology field, enhanced in current periods, due to conversion of its wild to engineer strain, suitable for bioprocesses utilization and also for different types of biochemical synthesis. Different yeast species identified due to known their genetic, regulatory mechanism and also competitive metabolic pathways. In this regards, different type of engineering approaches (for genetic or pathways modification), applied to construct the optimal and suitable cell factories for different types of bioprocesses as utilized in different sectors (foods with mineral or protein rich, bread, brewing, cosmetics, chemical, agriculture, pharmacy and distillation industries) via improving the quality of bio-products. Further, in silico designed based metabolic engineering technique showed the improvement in performance of yeast strain. System and synthetic biology with engineering approaches applied to further improve the yeast mediated bioprocesses as well as biochemical products formation for industrial or biotechnological application. Some bio-products such as functional bio-molecule, different types of alcoholic biofuels, organic acids and enzymes etc are good examples of yeast mediated biochemicals products, utilized more frequently in our life. Author will focus recent research and development on bio-product formation or bioprocesses with their regulatory control mechanism in different yeast strains.
Keywords: Bio-products